Localización de la industria agroalimentaria en Aragón - Climent López, Eugenio; Ruiz Budría, Enrique (Geographicalia, 2014)
Food industry is bifurcating into two zones of production: that of standardized or global foods, on one hand, that of specialized or local foods, on the other hand. This bifurcation can be explained by means of the worlds of production theory. On the light of this theory, locationof food industry in Aragon (Spain) is studied. Two location patterns have been identified: global food industries are concentrated within the urban-industrial agglomeration of Zaragoza, while local food production is located within specific rural areas linked to agricultural productions strongly embedded to territory.